Extrinsic and Existential Mortality Risk in Reproductive Decision-Making: Examining the Effects of COVID-19 Experience and Climate Change Beliefs - Gordon, David S. (Frontiers in Psychology, 2021)
While the COVID-19 pandemic has presented an immediate risk to human life around the world, climate change poses an arguably greater—although less immediate—threat to our species’ survival. Within the framework of life-history theory, this pre-registered study investigated whether extrinsic risk (i.e., external factors that pose a risk to an individual’s life, e.g., COVID-19) and existential risk (i.e., risks with outcomes that threaten the existence of humans as a species, e.g., climate change) had similar or different relationships with reproductive decision-making. A UK-representative sample of 325 participants between 18– and 35 years of age were asked to indicate their ideal number of children, ideal age to start having children, and whether their desire for a child had recently changed. Participants were asked about their experiences of COVID-19 and given a series of scales with which to assess their beliefs about climate change. In support of life-history theory, the study found evidence that knowing people who had been hospitalized with or died of COVID-19 was associated with a greater ideal number of children. Conversely, there was no clear evidence of a relationship between climate change beliefs and reproductive decision-making. The repercussions for understanding how we interpret and respond to different forms of mortality risk are discussed.